Нарушение клеточного звена общего иммунитета у больных с различными видами эндоцервикоза = Violation of the total cellular immunity in patients with different types of endocervicosis - Selskyy, P. R.; Furdela, M. Ya.; Selskyy, B. P. (Journal of Education, Health and Sport, 2016)
Selskyy P. R., Furdela M. Ya., Selskyy B. P. Нарушение клеточного звена общего иммунитета у больных с различными видами эндоцервикоза = Violation of the total cellular immunity in patients with different types of endocervicosis. Journal of Education, Health and Sport. 2016;6(4):31-38. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.49393 http://ojs.ukw.edu.pl/index.php/johs/article/view/3444 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 20.03.2016. Accepted: 05.04.2016. Нарушение клеточного звена общего иммунитета у больных с различными видами эндоцервикоза П. Р. Сельський, М. Я. Фурдела, Б. П. Сельський Государственное высшее учебное заведение “Тернопольский государственный медицинский университет имени И.Я. Горбачевского МОЗ Украины”, Тернополь, Украина Резюме Проведено иммунологическое исследование 51 больной с эндоцервикозом. В первую группу вошли все больные с эндоцервикозом, вторую – только с простым эндоцервикозом (31,4 %), в третью (37,2 %) – с заживающим эндоцервикозом, а четвертая группа (31,4 %) охватывала женщин с прогрессирующим эндоцервикозом. Анализ клеточного звена иммунитета проводился с помощью моноклональных антител к антигенам лимфоцитов CD3, CD4, CD8 и CD19. Содержание большинства фенотипов лимфоцитов крови обследованных женщин с эндоцервикозом отличалось от нормальных. У больных с эндоцервикозом наблюдалось значительное угнетение клеточного звена иммунитета. Средний уровень CD3-лимфоцитов составил – (46,0±0,7) % против (64,5±2,8) % в контрольной группе (р<0,05). Средний уровень CD4-лимфоцитов был также существенно снижен и составлял (30,2±0,3) % против (44,2±2,6) % в группе практически здоровых женщин (р<0,05), а среднее содержание CD8-лимфоцитов составляло (15,0±1,0) % против (22,9±2,0) % в группе контроля (р<0,05). Имело место и снижение соотношения Тh/Ts (иммунорегулирующий индекс CD4/CD8 составлял 1,9±0,1 против 2,3±0,1 у женщин контрольной группы) и уровня CD16-лимфоцитов (натуральных киллеров), среднее содержание которых составляло (10,0±0,3) % против (14,5±1,9) % в контрольной группе (р<0,05). Изменения уровня относительного количества Т-лимфоцитов коррелировали со степенью развития эндоцервикоза (r = - 0,94 – сильная обратная связь). Результаты исследований свидетельствуют о выраженных нарушениях иммунологического гомеостаза у больных эндоцервикозом, которые проявлялись Т-лимфопенией, снижением уровня натуральных киллеров, дисбалансом субпопуляционного состава Т-клеток, в основном за счет снижения циркулирующих Т-хелперов/индукторов, что приводило к снижению коэффициента CD4/CD8 и свидетельствовало о формирование вторичного иммунодефицита преимущественно по иммуносупрессорному варианту. В результате исследования клеточного иммунитета у больных с эндоцервикозом выявлено четкую связь между степенью иммунных нарушений и видом эндоцервикоза, причем существенные изменения были отмечены при прогрессирующем эндоцервикозе, в то же время при заживлении эндоцервикоза – большинство иммунных показателей находились в пределах нормы. Процент больных с иммуносупрессорным вариантом вторичного иммунодефицита у пациенток с прогрессирующим и стационарным эндоцервикозом имел тенденцию к повышению по сравнению с группой обследованных с заживающим эндоцервикозом, в то же время у последних значительно чаще встречался гипосупрессорный вариант вторичной иммунологической недостаточности, а при стационарном и прогрессирующем эндоцервикозе он не наблюдался. Таким образом, на основе проведенных исследований можно сделать вывод о существенном влиянии нарушения клеточного иммунитета на прогрессирование данного заболевания. Ключевые слова: шейка матки, предопухолевые заболевания, клеточный иммунитет, популяции лимфоцитов, иммунорегулирующий индекс, иммунологическая недостаточность, прогрессирование эндоцервикоза. Violation of the total cellular immunity in patients with different types of endocervicosis P. R. Selskyy, M. Ya. Furdela, B. P. Selskyy State Institution of Higher Education “I. Horbachevsky Ternopil State Medical University of the Ministry of Health of Ukraine” Summary Immunomorphological investigation of 51 patients with endocervicosis was carried out. The first group included patients with endocervicosis, the second group contained women with simple endocervicosis (31,4 %), the third (37,2 %) – patients with healing endocervicosis, and the fourth group (31,4 %) women had progressive endocervicosis. The analysis of cellular immunity was done with the help of monoclonal antibodies to antigens of CD3, CD4, CD8 and CD19 lymphocytes. The content of most blood lymphocytes phenotypes in examined women with endocervicosis was different from the normal. Patients with endocervicosis showed a significant inhibition of cell immunity. The average level of CD3-lymphocytes was 46,0±0,7 % compared to 64,5±2,8 % in the control group (p<0,05). The average level of CD4-lymphocyte count was also significantly reduced – 30,2±0,3 % compared to 44,2±2,6 % in the group of healthy women (p<0,05), and the average content of CD8-lymphocytes was lower (15,0±1,0 %) against control group (22,9±2,0 %) with p<0,05. There has been a decline in the ratio of Тh/Ts (immunoregulatory index CD4/CD8 was 1,9±0,1 compared to 2,3±0,1 in the women of the control group), as well as in the level of CD16-lymphocytes (natural killer cells) – 10,0±0,3 % vs 14,5±1,9 % in the control group (p<0,05). Changes in the relative number of T cells strongly correlated with the degree of endocervicosis development (r = - 0,94). Our research showed profound disruption of immunological homeostasis in patients with endocervicosis, and this disruption was manifested by T lymphopenia, reduced levels of natural killer cells, imbalance of T-cells subpopulations, mainly due to the decrease in circulating T helper/inducer cells, which led to a decrease in CD4/CD8 ratio and evidence of the formation of secondary immune deficiency, following the immunosuppressive scenario. The study of cellular immunity in patients with endocervicosis revealed a clear correlation between the degree of immune disorders and types of endocervicosis. The most significant changes were observed in case of progressive endocervicosis, while the majority of immune parameters were within normal limits in case of healing endocervicosis. The percentage of patients with immunosuppressive scenario of secondary immunodeficiency in patients with progressive and ongoing endocervicosis tended to increase compared with the group of examinees with healing endocervicosis. The patients with healing endocervicosis experienced hyposuppressive scenario of secondary immune deficiency, while in case of the ongoing and progressive endocervicosis this scenario was not observed. To summarize current research, we can make the conclusion about the significant influence of the disruption of the cellular immunity on the endocervicosis progress. Keywords: cervix, precancerous diseases, cellular immunity, lymphocyte populations, the immune regulatory index, immunologic failure, progression endocervicosis.